2015
DOI: 10.1038/mt.2015.31
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA Arid2-IR Is a Novel Therapeutic Target for Renal Inflammation

Abstract: Increasing evidence shows that microRNAs play an important role in kidney disease. However, functions of long noncoding RNAs (lncRNAs) in kidney diseases remain undefined. We have previously shown that TGF-β1 plays a diverse role in renal inflammation and fibrosis and Smad3 is a key mediator in this process. In this study, we used RNA-sequencing to identify lncRNAs related to renal inflammation and fibrosis in obstructive nephropathy induced in Smad3 wild-type and knockout mice. We found that Arid2-IR was a Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 33 publications
1
132
0
Order By: Relevance
“…Smad3 −/− and Smad3 +/+ bone marrow cells were harvested and transfected with (100 nM) nonsense control (siN05815122147, RIBOBIO) and siRNA against E4BP4 (5′-GAUGAGGGUGUAGUGGGCAAGUCUU-3′) on Days 0 and 4 as described previously53. The bone marrow cells were ex vivo differentiated into NK cells according to the protocol of Fathman et al 54…”
Section: Methodsmentioning
confidence: 99%
“…Smad3 −/− and Smad3 +/+ bone marrow cells were harvested and transfected with (100 nM) nonsense control (siN05815122147, RIBOBIO) and siRNA against E4BP4 (5′-GAUGAGGGUGUAGUGGGCAAGUCUU-3′) on Days 0 and 4 as described previously53. The bone marrow cells were ex vivo differentiated into NK cells according to the protocol of Fathman et al 54…”
Section: Methodsmentioning
confidence: 99%
“…shRNA-mediated downregulation of Miat (also known as Gomafu) in the medial prefrontal cortex of the brain promotes anxiety-like behaviors (75), while local siRNA-mediated downregulation of Munc, which is specifically expressed in skeletal muscle, impairs myogenesis (76). Additionally, the use of an shRNA to revert the upregulation of Arid2-IR in the mouse kidney following renal inflammation also reverts the biochemical signatures of this condition (77). Future work using mutant-and virus-mediated strategies will likely reveal additional phenotypes directly attributable to lncRNAs.…”
Section: Animal Models and Lncrna Functionmentioning
confidence: 99%
“…Since TGFβ signals via Smad3, this approach identified LNCRNAs involved in the Smad3 signalling pathway. It was found that ARID2-IR LNCRNA functions to block nuclear factor-κB (NF-κB) dependent renal inflammation [11]. There are currently no studies which have measured ARID2-IR in animal models of DKD.…”
Section: Lncrnas and Diabetic Kidney Diseasementioning
confidence: 99%